OSMOREGULATORY ABILITY OF PENAEUS MONODON (FABRICIUS) IN RELATION TO VARYING SALINITIES - Diwan, A D; Laxminarayana, A; Kakati, V S (Indian Journal of Fisheries, 2011)
Adult Penaeus monodon osmoregulated well between salinities 3 and 45%0 for 24 and 48 hour durationwith isosmotic pOints around .. 5 18.5%0 and .. 5 23.5%0 respectively. A duration of 48 hr is essential forprawns to adjust to the new medium. Influence of eyes talk removal on osmolal concentration of haemolymphwas studied. There was a significant decline in osmolal concentration in destalked prawns from4 to 18hr after eyestalk surgery performance, but later recouping effect was seen. In destalked prawnswhen eyestalk extract was administered, the level of osmolal concentration did not decrease but alwaysremained high throughout the experimental period. Probable reasons for such changes are discussed